Unilateral Laminotomy for Bilateral Microsurgical Decompression in Treating Multiple Spinal Stenosis - Wawan Mulyawan; Yudi Yuwono Wiwoho (Indoscholar, 2019)
Multiple spinal stenosis with significant signs and symptoms is one of the complex problems in spine pathology. For a simple reason, many spine surgeons do conservative decompressions, such as decompressive laminectomy or bilateral laminotomy and flavectomy, with one incision (preservation of lamina). Unilateral laminotomy in the lumbar area for bilateral access in spinal canal is quite rare and is performed for the treatment of multiple spinal stenosis. With this technique, microsurgical decompression is done with partial resection of the ipsilateral facet, the medial part of the laminar arch, and the partial contralateral facet, with the complete removal of the ligamentum flavum. By this methods, the aim for complete bilateral flavectomy and partial bilateral facetectomy are the key for the success of clinical improvements in treating multiple spinal stenosis.